2023
DOI: 10.3389/fmed.2022.904638
|View full text |Cite
|
Sign up to set email alerts
|

The association of periodontal diseases and Sjogren’s syndrome: A systematic review and meta-analysis

Abstract: BackgroundThe relationship between periodontal diseases and Sjogren’s syndrome were found inconsistent in current studies. Our objective is to clarify the relationship between periodontal diseases and Sjogren’s syndrome.MethodsA systematic review was performed and reported according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Electronic databases (EMBASE, PubMed, Web of Science, and Cochrane Library, from inceptions until 24 November 2021) were searched. The Newcastle-Ottawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
0
11
1
1
Order By: Relevance
“…However, there were also several studies in contrast with our results. Two systematic reviews with meta-analysis similarly reported that SS patients were more likely to suffer from PD or worse periodontal status, which was not in line with our results [ 23 , 25 ]. However, these two studies still did not examine the risk of developing SS among PD patients, and as kindly figured out by their authors, the reliability of these results was impaired by unsatisfied methodological quality of the primary studies in meta-analysis, high statistical heterogeneity with no explicit source, or selection and cofounding bias in observational studies.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…However, there were also several studies in contrast with our results. Two systematic reviews with meta-analysis similarly reported that SS patients were more likely to suffer from PD or worse periodontal status, which was not in line with our results [ 23 , 25 ]. However, these two studies still did not examine the risk of developing SS among PD patients, and as kindly figured out by their authors, the reliability of these results was impaired by unsatisfied methodological quality of the primary studies in meta-analysis, high statistical heterogeneity with no explicit source, or selection and cofounding bias in observational studies.…”
Section: Discussioncontrasting
confidence: 81%
“…Meanwhile, some key proinflammatory mediators that might drive a higher risk of PD are elevated in saliva extracted from patients with SS, such as IL-12, IL-6, and IL-17, indicating the possible existence of a shared etiopathogenesis among these two diseases [ 19 22 ]. Several recent meta-analyses also supported these findings [ 23 25 ]. However, there were also some studies reporting no link between PD and SS [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 58%
“…La asociación entre el síndrome de Sjögren y las afecciones gingivoperiodontales ha sido convalidada de manera categórica por numerosos estudios. Como ejemplo de esto, un metaanálisis publicado en el 2023 demostró con claridad que los pacientes que padecen síndrome de Sjögren poseen índices periodontales y gingivales más elevados que aquellos sanos, debido a la disminución de la secreción salival, aumentando sus chances de desarrollar enfermedad periodontal (Yang et al, 2023).…”
Section: Efectos De Los Cambios En Las Glándulas Salivales Sobre Los ...unclassified
“…As highlighted by a recent meta-analysis on the subject, performed on 21 studies with a total of 11,435 participants, SS patients could have an increased risk of being diagnosed with periodontitis [ 88 ]. However, as reflected by our systematic review and the conclusion of Yang’s meta-analysis, the results are highly heterogenous, meaning that so far, no definitive conclusion could be drawn [ 88 ]. Our review has illustrated a variety of approaches to the matter of increased risk in SS patients for periodontitis, generating, at times, conflicting results.…”
Section: Future Perspectivesmentioning
confidence: 99%